Construction of CRISPR/Cas9 expression vectors habouring gRNA targeted on SLIAA9 gene of tomato - Manh Minh, Bui; Hong Hanh, Ha; Thu Hien, Le Thi; Thu Hue, Huynh Thi (Vietnam Journal of Biotechnology, 2020)
Tomato (Solanum lycopersicum) is a nutritious fruit containing many secondary compounds with health benefits. The formation of tomato fruit through fertilization is controlled by auxin through Aux/IAA9 and ARF8 proteins. The mutated SlIAA9 gene leads to the parthenocarpic development of fruit or seedless tomato fruit. Nowadays, the CRISPR/Cas9 genome editing system is becoming increasingly popular in modifying desired genes on plant objects. In this study, gRNAs which target on tomato SlIAA9 gene were designed and inserted into CRISPR/Cas9 vectors. In addition, two strains of A. tumefaciens harboring pRGEB31-IAA9G2 and pRGEB32-IAA9G2 vectors carrying CRISPR/Cas9 expression system towards SlIAA9 gene in tomato were successfully created. The strain of A. tumefaciens harboring pRGEB31- IAA9G2 plasmid was used to develop transgenic tomato plants from Micro-Tom variety. PCR test showed that 5/14 plants had the presence of Cas9 gene in T0 plants. The transgenic plants have a normal morphology in comparation with the controls. The evaluation of mutant efficiency, type, and stability of mutations on the SlIAA9 will be conducted on next-generation plants when the mutations are stable and segregated into descendents.